2015
DOI: 10.1158/1541-7786.mcr-14-0424
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant microRNAs in Ovarian Cancer

Abstract: MicroRNAs (miRNAs/miRs) belong to a class of small non-coding RNAs that can negatively regulate messenger RNA (mRNA) expression of target genes. miRNAs are involved in multiple aspects of ovarian cancer cell dysfunction and the phenotype of ovarian cancer cells can be modified by targeting miRNA expression. miRNA profiling has detected a number of candidate miRNAs with the potential to regulate many important biological functions in ovarian cancer, but their role still needs to be clarified, given the remarkab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 74 publications
(113 reference statements)
2
74
0
2
Order By: Relevance
“…Correlations of genes previously identified to be associated with ovarian disease [3441] (Supplemental Table S13) with the transgenerational granulosa cell genes of this study identified a number of genes associated with ovarian disease, Figure 11 and Supplemental Table S14. A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Correlations of genes previously identified to be associated with ovarian disease [3441] (Supplemental Table S13) with the transgenerational granulosa cell genes of this study identified a number of genes associated with ovarian disease, Figure 11 and Supplemental Table S14. A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55].…”
Section: Discussionmentioning
confidence: 79%
“…Extensive reviews previously published have summarized the genes that have been associated with ovarian disease [3441]. These published ovarian disease-associated genes were compiled into a list of 416 genes that are listed in Supplemental Table S13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (16) reported that miRNA was involved in the occurrence and development of ovarian cancer drug resistance by studying a stem cell-like epithelial ovarian cancer line. Li et al (17) demonstrated that miRNA-27a was associated with ovarian cancer drug resistance, and the mechanism was that MDR1/P-GP gene regulated the HIPK2 gene.…”
Section: Discussionmentioning
confidence: 99%